HUBUNGAN PENGETAHUAN SISWI TENTANG VULVA HYGIENE DENGAN KEJADIAN KEPUTIHAN PADA SISWI SEKOLAH MENENGAH PERTAMA NEGERI 4 KOTA SUKABUMI WILAYAH KERJA PUSKESMAS KARANGTENGAH KOTA SUKABUMI - Wati Mulyawati; Fanny Sukmasary; Qorry Wahyuni Septica (JURNAL KESEHATAN INDRA HUSADA, 2022)
One of the adolescent problems is the lack of maintaining cleanliness in the female organs which can lead to several consequences, such as vaginal discharge in adolescents, including adolescents in Junior high School Students State 4 Sukabumi City. The purpose of this study was to determine the relationship between knowledge of vulvar hygiene and the incidence of vaginal discharge. Vaginal discharge is a condition in which the vagina secretes fluid or mucus. Vaginal discharge is not always a disease because there is also a normal vaginal discharge. This type of research is correlational with a cross sectional approach. The population is all students at hight School State 4 high School Students State 4 Sukabumi City, namely 289 students with a sample of 168 students and using the Proportional Stratification Random Sampling technique. There are 25 valid statement items out of 30 statement items. The reliability results of the 25 valid statement items are 0.630. Data collection techniques using questionnaires and statistical analysis using phi correlation. Based on the results of the study, it was found that the knowledge of respondents in the poor category was 118 respondents (70.2%) and the incidence of vaginal discharge had experienced vaginal discharge as many as 136 respondents (81%). Result p-value = 0.004. So this study shows that there is a relationship between students' knowledge of vulvar hygiene and the incidence of vaginal discharge. Based on the conclusion, there is a relationship between knowledge of vulvar hygiene and the incidence of vaginal discharge. It is hoped that the Karangtengah Health Centre will further optimize the youth health program by providing counseling to schools regarding clean behavior that must be owned by every school member.